Tilted Arch; Implementation of Additive Manufacturing and Bio-Welding of Mycelium-Based Composites - Behzad Modanloo; Ali Ghazvinian; Mohammadreza Matini; Elham Andaroodi (Biomimetics, 2021)
Bio-based materials have found their way to the design and fabrication in the architectural context in recent years. Fungi-based materials, especially mycelium-based composites, are a group of these materials of growing interest among scholars due to their light weight, compostable and regenerative features. However, after about a decade of introducing this material to the architectural community, the proper ways of design and fabrication with this material are still under investigation. In this paper, we tried to integrate the material properties of mycelium-based composites with computational design and digital fabrication methods to offer a promising method of construction. Regarding different characteristics of the material, we found additive manufacturing parallel to bio-welding is an appropriate fabrication method. To show the feasibility of the proposed method, we manufactured a small-scale prototype, a tilted arch, made of extruded biomass bound with bio-welding. The project is described in the paper.